Balancing Give and Take: Funding and Accountability in Public Higher Education - Ronca, Justin M.; Weerts, David J.; Trostel, Philip A.; St. John, Edward P. (My University, 2007)
Many of the challenges facing postsecondary education today are rooted in lack of resources and money. As state legislatures wrestle with the growing costs of Medicaid, social services, corrections, and K-12 education, state support for higher education remains stagnant. This forces public universities to look to other sources for revenue, including federal and private grants, alumni donations, student tuition and fees, and entrepreneurial enterprises. In turn, these constituent groups place greater expectations and demands on public colleges and universities, further stretching already limited resources. Within this landscape of numerous and sometimes conflicting demands, colleges and universities need to remain accountable to the state government and serve the public good in order to ensure a sufficient and stable level of public funding. At the same time, state governments must maximize the use of limited funds in order to reap the greatest benefits of investing in higher education. To help states and their universities accomplish these monumental tasks, this forum features some of the latest postsecondary education research addressing three fundamental questions: 1. How do states benefit from investing in higher education? 2. What should public universities do to serve the public good and therefore earn and ensure state funding? 3. How do we maximize the investment of limited tax dollars in higher education?
Keywords: Outreach, Engagement, and the Public Good; Finance and Economics